Policy Evaporation in the Himalayas: Climate Adaptation Gaps in Nepal’s Karnali Basin - Baral, Navaraj; Neupane, Gokul Prasad (NPRC Journal of Multidisciplinary Research, 2026)
Background: The Upper Karnali River Basin in Nepal is highly susceptible to climate-related hazards. Despite the existence of national adaptation policies such as the National Adaptation Programme of Action (NAPA) and the Local Adaptation Plans of Action (LAPA), a persistent gap remains between policy design and local-level implementation. Objectives: This study examines the adaptation policy–implementation gap across three municipalities representing the upstream (Pachaljharana), midstream (Bhairavi), and downstream (Jagannath) sections of the basin. It identifies the key barriers to effective adaptation and explores spatial variations in hazard exposure, impacts, and participatory responses. Methods: A mixed methods approach was employed, incorporating household surveys, key informant interviews, focus group discussions, and policy document analysis to assess adaptation practices, governance processes, and community participation across the three municipalities. Findings: The results reveal significant spatial variation in climate hazard exposure: water scarcity dominates upstream, landslides in the midstream, and flooding downstream. Agricultural loss and livestock decline are the most severe economic impacts, while water scarcity and erosion of traditional livelihoods are the dominant social impacts. Traditional coping strategies remain widely practiced, but participation in formal adaptation activities—such as early warning systems, data recording, and training—is very low. Governance barriers include weak inter-administrative coordination, inadequate financing, elite capture, and the exclusion of Dalits, women, and landless households. National policies are well designed but poorly implemented locally. Conclusion: Bridging the adaptation gap requires spatially targeted planning, integration of traditional knowledge, investment in community-based early warning systems, and institutional reforms that ensure marginalized groups actively participate in decision-making rather than merely contributing labour. Novelty: This study is the primary municipality-level comparison across a Himalayan basin to quantify participatory exclusion and explicitly link hydropower development to local adaptation failures.